DEMAGOGI DAN KEKERASAN AGAMA DALAM SISTEM DEMOKRASI DI INDONESIA - Tahir, Masnun (Analisis: Jurnal Studi Keislaman, 2011)
Democracy in Indonesia does not emerge political behavior but on the contrary it appears political ignorance that disregards moral sides of politics.  Religion that should be a base for political ethics is only more performed as symbolic. Finally, politician be a demagogy, who sowed religious values that are not conducted. This attitude on the top side caused social frustration and spread violence on behalf  of religion. This case is caused by regarding of radical group that the rulers have insulted religion, and because of  that, they proper to toppled by any manner. With the result that democratic portrait yielded violence that caused by politician’s performing and a short answer given by radical group. Thus, system of  democracy in Indonesia becomes damage and need to reorganize.